Confronting Digital Dilemmas in Translator and Interpreter Training - Djovčoš, Martin | https://orcid.org/0000-0003-2487-4151 (Taylor & Francis, 2026)
This collection explores the challenges and opportunities brought on by developments in emergent technologies for translator and interpreter training. Given the growing role of language professionals as mediators in an increasingly fragmented and globalized world, this book offers an in-depth look at the present and future of translator and interpreter training amidst these changes. Featuring perspectives from established and up-and-coming scholars, the volume is organized in three sections taking in turn different dimensions of the current training landscape. These parts consider key topics including theoretical foundations and pedagogical innovations, ethical considerations and social responsibility, and ways forward for adapting training programs to better grapple with new tools. Taken as a whole, this book will be a useful resource for students and scholars in translation and interpreting studies, as well as practicing professionals.